New Species of Blindsnakes (Squamata: Gerrhopilidae) from the offshore islands of Papua New Guinea - Kraus, Fred (Zootaxa, 2017)
I describe four new species of blindsnake of the genus Gerrhopilus from islands off the southeastern tip of New Guinea and from New Ireland to the northeast. All have ventral keels on the rostral scale, and most have previously been assigned in their respective museum collections to the species G. depressiceps. Examination of available specimens shows G. depressiceps to be a composite of species, and I emend the diagnosis of that species based on the holotype and one additional specimen from northeastern New Guinea. The species described as new here differ from G. depressiceps and from each other in a series of features, including shape of the snout, shape of the rostral scale, numbers of mid-dorsal scale rows, reduction patterns in longitudinal scale rows, body mass, degree of eye development, and color pattern. The new species all inhabit islands remote from the known range of G. depressiceps on New Guinea and have likely been separated from that species for millions of years.